Para-athlete talent transfer - personal and environmental factors - Green, A. (University of the Sunshine Coast, 2024)
Talent transfer, occurring when an experienced athlete transfers to a new sport with the goal of attaining high-performance levels, has contributed significantly to Australia`s Paralympic success. Despite the prevalence of talent transfer athletes in para-sport, this practice has primarily occurred informally, with knowledge and implementation derived from anecdotal sources rather than empirical evidence. Furthermore, of the available literature regarding talent transfer pathways, the majority is limited to studying non-para-athletes and sports. Due to the unique characteristics associated with para-sport, and the additional challenges para-athletes face when striving for elite sporting success, the generalisability of this prior research to para-sport is limited. Thus, the overarching aim of this thesis was to develop an empirically grounded framework of the factors that influence talent transfer in para-sport, to improve the efficiency and effectiveness of para-athlete talent transfer.